Street-based survey on drug patterns in four Croatian cities - Raboteg-Šarić, Zora (Array, 1999)
The aims of the research described in this chapter were to analyse patterns of drug consumption, psychological and the social profile of drug users, their mobility and social networks and help-seeking patterns. The research was carried out in Zagreb, Split, Pula and Zadar with 279 drug users. A combination of qualitative and quantitative methodology was applied. Data was collected through semi-structured interviews and short questionnaires during direct contact with drug users in their natural surroundings. Data analyses included comparisons between heroin users and soft drug users as well as between the four study sites. Based on the general and specific characteristics of the local drug scene, strategies that contribute to decreasing the interest of drug users in using addictive substances and initiate their involvement in current forms of treatment were recommended.